Lean Food Supply Chain Management Within Agro-Food Distributors In Malaysia - Kowang, Tan Owee; Yun, Chung Pei; Hee, Ong Choon; Fei, Goh Chin; Yew, Lim Kim; Hoo, Wong Chee; Teck, Tan Seng (International Journal of Psychosocial Rehabilitation, 2020)
The Malaysia National Agro-Food Policy (DAN) 2011-2020 was introduced to ensure the agro-food supply in Malaysia is ascertained. The main focus of DAN is to improve the self-sufficiency level of agro food. However, another challenge in food security is to ensure the food that available is delivered from farm to consumers effectively, or namely the management of food supply chain (FSCM). As such, one of the core focuses in the Malaysia Agro Food Policy 2.0 is to capitalise the entire agro food sector value chain in order to improve the performance of agro FSCM. This only could be done via high degree of coordination and continuous value creation across all activities in the agro food supply chain, which is in line with the principle of Lean. Hence, this study aims to assess the implementation level of Lean Food Supply Chain Management (LFSCM) practices and performance within agro-food distributors in Malaysia, and to assess the relationship between both. The research is quantitative based. Five LFSCM performance attributes and four LFSCM practices were identified from literature review and formulated into a survey questionnaire which was answered by 50 agro-food distributors within Malaysia. Data collected is analysed via descriptive analysis and Pearson correlation. Analysis result reveals that LFSCM practices within agro-food distributors in Malaysia tends to focus on soft lean practices, in addition all LFSCM practices are positively correlated with LFSCM performance. Finding from the study implies that Lean concept and principle could be applied in agriculture or agro-food industry as the approach to improve performance.